Thermal history and microstructure during friction stir welding of Al–Mg alloy. Issue 1 (September 2016) - Sheikh-Ahmad, J.; Ozturk, F.; Jarrar, F.; Evis, Z.
Abstract In this study, a commercial aluminum–magnesium alloy was friction stir welded (FSW) at a constant rotational speed of 1016 rpm and different welding speeds from 50 to 400 mm/min. Temporal thermal histories of the process were recorded at different locations from the weld line and transformed to spatial temperature distribution near the weld line. Tensile and microhardness measurements were also performed and the microstructure in the weld zone was investigated. Results of this revealed that an increase in welding speed causes a decrease in the stir zone temperature, which leads to a decrease in the stir zone grain size. As a result, both tensile strength and hardness increased with an increase in welding speed. Dynamic recrystallization and post-weld static grain growth were the controlling factors of stir zone grain size. The grain size correlated closely with the Zener–Hollomon parameter. Slow cooling resulted in larger post-weld grain size than what is normally expected.